Dose map blood irradiator dosimetry system: customized blood equivalent phantom and gafchromic EBT-XD film - Saiful Fazad, Adiela; Nasir, Muhammad Amir; Noor, Noramaliza Mohd Noor (Longe Medikal, 2023)
Blood irradiation is done to sterilize and cease donor T-lymphocytes functionality to avoid Transfusion Associated-Graft Versus Host Disease (TA-GVHD). Dose mapping is the primary means of ensuring that the irradiation process is being conducted correctly. The aim of this study is to measure the minimum, maximum and central absorbed gamma radiation dose delivered at the newly customized blood equivalent phantom using a Gafchromic EBT-XD film. A Gammacell 3000 Elan Blood Irradiator with Cesium-137 source was used. To obtain the dose calibration curves, the films were placed at the center of a phantom and irradiated with the dose range from 5 Gy to 35 Gy with one unirradiated film as a control. The dose calibration curve was plotted using red, green and blue channels. While, for the dose mapping measurement, the irradiation exposure of 9.03 minutes was used to deliver a central dose of 25 Gy to the film. The response of the film will be compared with the GC Dose Mapping Report 2022 which used a water equivalent medium as a phantom. For the calibration curve, the red channel of the film was utilized in this study as it had a higher signal than the other channel. The doses obtained at central, minimum and maximum using EBT-XD film with customized blood equivalent phantom were in agreement with that obtained from GC Dose Mapping Report 2022 to be within ±7.6, ±8.51 and ±9.95 respectively. We concluded that the customized blood equivalent phantom together with EBT-XD film has a potential to map the dose in blood irradiator accurately. The doses obtained from EBT-XD film were in the range of doses needed to inhibit the proliferation of the T-lymphocytes with central, minimum and maximum doses were 26.9 Gy, 17.2 Gy and 35.7 Gy respectively.